2004
DOI: 10.1097/01.ju.0000138085.19352.b5
|View full text |Cite
|
Sign up to set email alerts
|

Pig Kidney: Anatomical Relationships Between the Intrarenal Arteries and the Kidney Collecting System. Applied Study for Urological Research and Surgical Training

Abstract: Although the results of renal and intrarenal anatomy in pigs could not be completely transposed to humans, many similarities in the pig and human intrarenal arteries support its use as the best animal model for urological procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 21 publications
(36 reference statements)
8
103
0
4
Order By: Relevance
“…Although the swine is the most adequate model for comparison to human kidney anatomy and physiology 13,21 , this is still an experimental setting and different from the clinical setting. Further, these animals were healthy individuals, without renal tumor or any other medical condition which, again, does not represents the patients submitted to partial nephrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Although the swine is the most adequate model for comparison to human kidney anatomy and physiology 13,21 , this is still an experimental setting and different from the clinical setting. Further, these animals were healthy individuals, without renal tumor or any other medical condition which, again, does not represents the patients submitted to partial nephrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…However, two or more branches have been reported in the dog (Christensen 1952;Khamanarong et al 2004), while it was reported that the primary division of the pig renal artery forms a cranial and a caudal branch in 93.4% of cases (Pereira-Sampaio et al 2004). Similar to reports in rats (Fuller and Huelke 1973) and dogs (Khamanarong et al 2004;MarquesSampaio et al 2007), we observed the dorsal and ventral branches of renal arteries to be divided as cranial and a caudal segmental arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pig model is the most similar to human anatomy and physiology 15,29 , this is still an experimental setting and different from the clinical setting. These animals were healthy, without renal tumors or any other medical condition.…”
Section: ■ Discussionmentioning
confidence: 99%